2020
DOI: 10.1111/jog.14629
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin D‐calcium supplementation on metabolic profile and oxidative stress in gestational diabetes mellitus: A randomized controlled trial

Abstract: Aim To assess role of vitamin D‐calcium supplementation on the metabolic profile and oxidative stress in women with Gestational Diabetes Mellitus (GDM) controlled on diet. Methods A randomized controlled trial was conducted at a tertiary care teaching hospital. Seventy women diagnosed as GDM at 24–28 weeks of gestation, controlled on a diabetic diet, were randomized to receive either vitamin D 1000 IU and calcium 1000 mg (group A, n = 34) or vitamin D 250 IU and calcium 500 mg (group B, n = 36) daily for 6 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Among these alternative approaches, investigations identified that some of them would have a positive influence only on the attenuation of inflammatory processes and oxidative stress, such as selenium [ 165 ], olive oil [ 166 ], fish oil [ 167 ], and soy oligosaccharide [ 168 ], and others only on optimizing insulin sensitivity or by decreasing insulin resistance, such as pepper with capsaicin [ 169 ]; mugwort [ 170 ]; the dietary approaches to stop hypertension (DASH) diet [ 171 ]; co-supplementation of magnesium, zinc, calcium, and vitamin D [ 172 ]; vitamin D supplementation associated with evening primrose oil [ 173 ] and ginger [ 174 ]. Co-supplementation of vitamin D and calcium [ 175 , 176 ], in addition to co-supplementation of zinc and vitamin E [ 177 ], cod liver oil [ 178 ], flaxseed oil [ 179 ], and selenium [ 180 ] participate positively to reduce inflammatory processes, oxidative stress, and insulin resistance, contributing favorably to normal serum glucose levels.…”
Section: Alternative Therapies In Gdmmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these alternative approaches, investigations identified that some of them would have a positive influence only on the attenuation of inflammatory processes and oxidative stress, such as selenium [ 165 ], olive oil [ 166 ], fish oil [ 167 ], and soy oligosaccharide [ 168 ], and others only on optimizing insulin sensitivity or by decreasing insulin resistance, such as pepper with capsaicin [ 169 ]; mugwort [ 170 ]; the dietary approaches to stop hypertension (DASH) diet [ 171 ]; co-supplementation of magnesium, zinc, calcium, and vitamin D [ 172 ]; vitamin D supplementation associated with evening primrose oil [ 173 ] and ginger [ 174 ]. Co-supplementation of vitamin D and calcium [ 175 , 176 ], in addition to co-supplementation of zinc and vitamin E [ 177 ], cod liver oil [ 178 ], flaxseed oil [ 179 ], and selenium [ 180 ] participate positively to reduce inflammatory processes, oxidative stress, and insulin resistance, contributing favorably to normal serum glucose levels.…”
Section: Alternative Therapies In Gdmmentioning
confidence: 99%
“…Regarding micronutrients, isolated selenium supplementation, as well as co-supplementation of vitamin D + calcium and zinc + vitamin E, also led to the attenuation of the expression of pro-inflammatory cytokines and RONS [ 165 , 175 , 176 , 177 ]. Selenium is a trace element that can alleviate the inflammatory response by inhibiting the NF-κβ signaling pathway and TLR through the expression of PPAR-γ, which is a complementary way to attenuate insulin resistance and to improve the performance of glucose transporters (GLUT) and neutralize RONS [ 165 ].…”
Section: Alternative Therapies In Gdmmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium has several beneficial effects, but the effect of dietary magnesium on glucose metabolism during pregnancy has not been studied much. In one small diet-controlled, randomized trial of 1000 IU vitamin D and 1000 mg calcium supplementation versus 250 IU vitamin D and 500 mg calcium supplementation in women with GDM, the group that received the largest doses had significant reductions in several markers of glucose metabolism, including fasting glucose and insulin concentrations after six weeks [ 36 ]. The lower doses of these supplements also reduced fasting glucose but had no effect on insulin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the association between VD status and pregnancy complications are still controversial. On the one hand, some studies indicated that the alteration of VD was associated with a variety of adverse pregnancy outcomes, especially GDM [8][9][10]. On the other hand, some studies failed to correlate VD status with the above-mentioned consequences [11,12].…”
Section: Introductionmentioning
confidence: 99%